The Usefulness of Hybrid Security Classifications: Evidence from Redeemable Preferred Stock - Kimmel, Paul; Warfield, Terry D. (The Accounting Review, 1995)
[This study uses the relation between firm leverage and systematic risk to provide empirical evidence on the economic substance of a hybrid security: redeemable preferred stock (RPFD). The tests are conducted on 239 firms with RPFD outstanding between 1979 and 1989 and examine variation in this relation conditioned on the magnitude of RPFD as an element of firms' capital structures. The empirical results suggest that, despite mandatory redemption payments, RPFD does not have a debt-like impact on systematic risk and that the market perception of a hybrid security is conditioned on attributes such as voting rights and conversion features. Thus, dichotomous classification of hybrid securities may lack representational faithfulness to the economic substance of these securities, as measured by their effects on systematic risk. More generally, it may be difficult for the FASB to develop a comprehensive classification rule for hybrid securities without requiring additional disclosure of important security attributes.]